The intervention effect of Aitongxiao prescription on primary liver cancer rats was evaluated based on high-throughput miRNA sequencing and bioinformatics analysis - Xu, Lijing; Cheng, Jinlai; Li, Zhuoxian; Wen, Xiaoyu; Sun, Yuhao; Xia, Meng; Leng, Jing (Frontiers in Oncology, 2023)
Aitongxiao Prescription (ATXP) is a traditional Chinese medicine prescription used in the clinic to treat primary liver cancer (PLC) for decades. However, the mechanism of ATXP in treating primary liver cancer has not been fully elucidated. The purpose of this study was to test the liver protective effect of ATXP on the PLC rat model and to explore its potential mechanism from the perspective of serum exosomal miRNAs. Six of the 50 SPF male SD rats were randomly taken as the control group; the remaining rats were induced by intraperitoneal injection of DEN to establish a primary liver cancer model. The modeled rats were randomly divided into the model group and the ATX group. After 4 weeks of ATXP intervention, plasma biochemical indexes, and histopathological methods were used to evaluate the protective effect of ATXP on the liver. The plasma exosomes were isolated and extracted, and identified by transmission electron microscopy, nanoparticle tracking analysis, and WB. Exosomal miRNAs were screened out with significantly differentially expressed miRNAs by Illumina sequencing, to explore therapeutic targets of ATXP, and conduct functional analysis. The results showed that the treatment of ATXP could significantly lower the liver function of plasma and alleviate liver pathological injury in PLC rats. Furthermore, plasma exosomes were isolated and identified. According to the results of the GO and KEGG analyses, they were associated with biological processes and covered multiple signaling pathways (PI3K-Akt and MAPK signaling pathways). Besides, they are capable of suppressing liver cancer cell function(proliferation, apoptosis, necrosis, inflammation, and angiogenesis). The interaction between miR-199a-3p and MAP3K4 was determined by bioinformatics methods and dual luciferase reporter gene detection, which confirmed that MAP3K4 was the target gene of miR-199a-3p. In conclusion, ATXP protects the liver from DEN-induced PLC, which may be relevant to the regulation of plasma exosome miR-199a-3p.